Breast Cancer Epidemiology - Li, Christopher; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
As the most common cancer diagnosed among women world-wide, breast cancer is a disease of considerable public health importance. The number of established and hypothesized risk factors for breast cancer exceeds that of any other cancer resulting in a rich, but complicated and often conflicting literature on the epidemiology of this disease. Our understanding of factors that contribute to breast cancer risk, as well as the biology and molecular basis for this common disease, has greatly increased over the past few decades. This book provides a comprehensive review and critical assessment of the epidemiology literature on all major aspects of breast cancer incidence and mortality, etiology, and outcomes. Chapters are written by internationally recognized leaders in the field and provide a timely review of traditional etiologic risk factors, as well as more recently evaluated exposures. Several chapters are also devoted to clinical aspects of breast cancer including screening, diagnosis and treatment, and survival. As a result, this is the most up-to-date and comprehensive book on breast cancer epidemiology available.
Global Burden of Breast Cancer -- Breast Cancer Biology and Clinical Characteristics -- In situ Breast Cancer -- Endogenous Hormones -- Exogenous Hormones -- Reproductive Factors -- Physical Activity and Anthropometric Factors -- Diet and Nutrition -- Environmental and Occupational Exposures -- Shift Work and Circadian Disruption -- Non-Hormonal Medications and Chronic Diseases -- Male Breast Cancer -- Inherited Predisposition: Familial Aggregation and High Risk Genes -- Common Genetic Susceptibility Loci -- Mammographic Density as a Potential Surrogate Marker for Breast Cancer -- Breast Cancer Screening -- Principles of Breast Cancer Therapy -- Breast Cancer Outcomes.
Keywords: Medicine; Oncology; Human genetics; Medical laboratories; Microbiology; Medical virology; Biomedicine; Cancer Research; Human Genetics; Laboratory Medicine; Medical Microbiology; Molecular Medicine; Virology